Penicillin allergy: optimizing diagnostic protocols, public health implications, and future research needs. Issue 4 (August 2015) - Macy, Eric
Abstract : Purpose of review: Unverified penicillin allergy is being increasingly recognized as a public health concern. The ideal protocol for verifying true clinically significant IgE-mediated penicillin allergy needs to use only commercially available materials, be well tolerated and easy to perform in both the inpatient and outpatient settings, and minimize false-positive determinations. This review concentrates on articles published in 2013 and 2014 that present new data relating to the diagnosis and management of penicillin allergy . Recent findings: Penicillin allergy can be safely evaluated at this time, in patients with an appropriate clinical history of penicillin allergy, using only penicilloyl-poly-lysine and native penicillin G as skin test reagents, if an oral challenge with amoxicillin 250 mg, followed by 1 h of observation, is given to all skin test negative individuals. Summary: Millions of individuals falsely labeled with penicillin allergy need to be evaluated to safely allow them to use penicillin-class antibiotics and avoid morbidity associated with penicillin avoidance. Further research is needed to determine optimal protocol(s). There will still be a 1–2% rate of adverse reactions reported with all future therapeutic penicillin-class antibiotic use, even with optimal methods used to determine acute penicillin tolerance. Only a small minority of these new reactions will be IgE-mediated.